2019
DOI: 10.1080/10942912.2019.1701011
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetic of anthocyanins from rose ( Rosa rugosa ) as prepared by microencapsulation in freeze-drying and spray-drying

Abstract: In this work, anthocyanin of rose residue was microencapsulated, using spray-drying (1:1 (w/w) of GA to MD, the inlet air temperature was170°C, the drying airflow rate was 5.0 m 3 /min, feed rate was 0.36 L/h) and freezedrying (processing 48 h at −52°C, vacuum degree was 0.45 mbar) with gum arabic and maltodextrin as external materials. The total phenolic content (TPC), anthocyanin content (ACN), antioxidant activity, moisture content, water activity (A w), solubility, hygroscopicity, colorimetric property, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
4
23
2
Order By: Relevance
“…The anthocyanin contents for samples from convection oven was lower might due to the penetration of heat through the encapsulating agents thus causing anthocyanin degradation. The results of total anthocyanin contents for Yu and Lv (2019) was in contrast with the current study might due to the different encapsulating agents used from the same drying technique (freeze dryer).…”
Section: Total Flavonoid Contentscontrasting
confidence: 99%
See 2 more Smart Citations
“…The anthocyanin contents for samples from convection oven was lower might due to the penetration of heat through the encapsulating agents thus causing anthocyanin degradation. The results of total anthocyanin contents for Yu and Lv (2019) was in contrast with the current study might due to the different encapsulating agents used from the same drying technique (freeze dryer).…”
Section: Total Flavonoid Contentscontrasting
confidence: 99%
“…Table 3 indicates that the total anthocyanin content found to be higher in ultrasonic spray dried treatment, followed by oven-dried treatment and freeze dried treatment. This result was found to be in contrast with total anthocyanin contents for freeze dried rose (Rosa rugose) was higher than spray dried powders (Yu and Lv, 2019). This might due to different morphology structure produced from the different sample but the same drying technique.…”
Section: Total Flavonoid Contentsmentioning
confidence: 75%
See 1 more Smart Citation
“…Murali et al [48] also reported a 22-25% higher anthocyanin content for freeze-dried microcapsules loaded with black carrot juice, with the EE ranging from 80.81 to 98.51% for FD and 60.04 to 82.48% for SD. Yu and Lv [49], who attempted to microencapsulate rose residue anthocyanins, showed that the anthocyanin and total phenolic compound retention were, respectively, 91.44% and 95.12% for FD while 75.85% and 86.00% for SD.…”
Section: Freeze Dryingmentioning
confidence: 99%
“…The Mal-FD showed the highest lightness (L*) and the MalGA-TD appeared the highest darkness in this experiment. The dark appearance might be affected by the light scattering properties of the empty spaces after the sublimation of water in the system [22]. The color of all encapsulated extracts powder was different depending on drying methods.…”
Section: Physicochemical Properties Of Encapsulated Chayote and Kohlrabi Extracts Powdermentioning
confidence: 99%